Чинники подолання "цифрової нерівності": світовий досвід та можливості для України - Єршова, О.Л. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The article describes the factors, features and aspects of the "digital divide", the consequences for people in the community; ways to overcome it are suggested; international statistics for Ukraine on this issue are analyzed. The main features of the information and the digital divide in the network communications structure are clarified and commented; the availability of information and the digital divide in the Ukrainian segment of network communications is investigated.